Type 2 diabetes mellitus is associated with increased risk of pancreatic cancer: A veteran administration registry study. (14th December 2016) - Makhoul, Issam; Yacoub, Abdulraheem; Siegel, Eric
Background: The etiology of pancreatic cancer remains elusive. Several studies have suggested a role for diabetes mellitus, but the magnitude of its contribution remains controversial. Objectives: Utilizing a large administrative database, this retrospective cohort study was designed to investigate the relationship between type 2 diabetes mellitus and pancreatic cancer. Patients and design: Using the Veterans Integrated Services Network 16 database, 322, 614 subjects were enrolled in the study, including 110, 919 with type 2 diabetes mellitus and 211, 695 diabetes-free controls matched by gender, year of birth and healthcare facility. Results: A significantly higher incidence of pancreatic cancer was observed in patients with type 2 diabetes mellitus, with an adjusted hazard ratio (95% confidence interval) of 2.17 (1.70–2.77) for type 2 diabetes mellitus compared to controls (p < 10 −9 ) after controlling for the matching factors. Conclusion: The association between type 2 diabetes mellitus and pancreatic cancer was statistically significant and may, in part, explain the rising incidence of pancreatic cancer.